Avaliação da resistência à tração de pinos de fibra de vidro: influência da utilização de pinos anatômicos em raízes com e sem aplicação de laser - Aquino, Douglas Hernandez de [UNESP] (2013)
The purpose of this study was to evaluate the effect of rebasing of fiber glass (customization pin) and laser application in the roots of the tensile strength. The bovine roots were divided into four groups: G1 - pin glass fiber without reline and without application of the laser G2 - pin fiberglass and relining without use of laser, G3 - pin glass fiber with and without relining laser application, and G4 - pin reline glass fiber and laser application. After extraction, the bovine incisors were stored in aqueous 2 % formaldehyde, pH 7 for 30 days, then scraped with periodontal curettes number 11-12 and cleaned with a jet of baking soda and water. The teeth were then stored in saline solution at 0,9% and selected teeth with straight roots and the like and getting sectioned 17mm standardized root. After selection, the tooth were filled and prepared its channels to a depth of 12 mm. After removal procedure, the pipes were extended and applied to the roots of the received laser according to the experimental groups. After cementing pins fiberglass test was performed tensile testing machine Universal - EMIC - DL 3000 model with axial tensile loading at 0.5 mm/min. The results in kgf underwent statistical analysis- ANOVA and Tukey test. The results showed that the best approach allows customization of the prefabricated walls of the conduit with the decreasing cementation line, increasing the frictional retention and becoming more effectively against the walls of the dental cement reducing the risk of blistering. Allied to this fact the cleaning of ducts with efficient removal of debris provided by the application of the Er, Cr: YSGG assists in improving the adhesion of intracanal retainers